Monitoring Conservation of Forest in Protected Areas using Remote Sensing Change Detection Approach: a Review (2022)
Abstract: Deforestation and fragmentation threaten biodiversity owing to their impacts on many species. To prevent and minimise the problem, protected areas have been created with the aim of conserving biodiversity, and parts of continental territories have been designated for this purpose. However, these areas are not exempt from forest loss and can be directly and indirectly disturbed by surrounding territories, natural disasters, climate, and human actions. In addition, the management quality of many protected areas is unknown. Thus, forest change detection using remote sensing data has been implemented as an approach to assess forest loss in conservation areas, since it generates spatio-temporal information about the protected forest area, which can then be used to improve forest management and decision making. This article reviews the approaches that have been implemented to study forest changes in protected areas. © 2022, Pleiades Publishing, Ltd.